Bit Record Analysis for Bits Evaluating and Selection - Amel Habeeb Assi, Ass. Lect. (Journal of Engineering, 2017)
The bit record is a part from the daily drilling report which is contain information about the type and the number of the bit that is used to drill the well, also contain data about  the used weight on bit  WOB ,revolution per minute RPM , rate of penetration ROP, pump pressure ,footage drilled and bit dull grade. Generally we can say that the bit record is a rich brief about the bit life in the hole. The main purpose of this research is to select the suitable bit to drill the next oil wells because the right bit selection avoid us more than one problems, on the other hand, the wrong bit selection cause more than one problem. Many methods are related to bit selection, this research is familiar with four of those methods, which they are: specific energy method, bit dullness way, cost per foot method, offset well bit record and geological information way. Five oil wells have been studied in Rumaila Oil Field in South of Iraq which they are R-531, R-548, R-536, R-544 and R-525. The wells R-531, R-536 and R-525 are vertical wells; the wells R-548 and R-544 are directional wells at angle of inclination 8.79◦ and 16.62◦ respectively.